2022
DOI: 10.1007/s10902-022-00506-5
|View full text |Cite
|
Sign up to set email alerts
|

Choice Matters More with Others: Choosing to be with Other People is More Consequential to Well-Being than Choosing to be Alone

Abstract: Stable social relationships are conducive to well-being. However, similar effects are not reported consistently for daily social interactions in affecting episodic (experiential) subjective well-being (ESWB). The present investigation suggests that the choice of being in a social context plays an important moderating role, such that social interactions increase ESWB only if taken place by one's choice. Moreover, it is argued that choice matters more in a social context than in an alone context because experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
(97 reference statements)
2
11
0
Order By: Relevance
“…It also fits empirical research on solitude-seeking and well-being: A higher desire for solitude was associated with decreased PA in middle-aged adults (but not in older adults, Lay, Pauly, et al, 2020). People had more positive and less negative affective experiences in chosen as compared to unchosen solitary activities, and in chosen compared to unchosen social activities (Tse et al, 2022;Uziel & Schmidt-Barad, 2022). From a theoretical standpoint, people may seek out solitude voluntarily to attain broad benefits to well-being through creative or spiritual pursuits, self-discovery, increased productivity, or recuperation (Long et al, 2003).…”
Section: Social Contact Social Desire and Momentary Affectsupporting
confidence: 75%
See 1 more Smart Citation
“…It also fits empirical research on solitude-seeking and well-being: A higher desire for solitude was associated with decreased PA in middle-aged adults (but not in older adults, Lay, Pauly, et al, 2020). People had more positive and less negative affective experiences in chosen as compared to unchosen solitary activities, and in chosen compared to unchosen social activities (Tse et al, 2022;Uziel & Schmidt-Barad, 2022). From a theoretical standpoint, people may seek out solitude voluntarily to attain broad benefits to well-being through creative or spiritual pursuits, self-discovery, increased productivity, or recuperation (Long et al, 2003).…”
Section: Social Contact Social Desire and Momentary Affectsupporting
confidence: 75%
“…Volition can be considered a precondition for a match between social contact status and momentary social desire and is therefore related to the social dynamics analyzed in this study. Higher volition of social interaction status has consistently been linked to higher well-being (Hall et al, 2021;Hall & Merolla, 2020;Uziel & Schmidt-Barad, 2022).…”
Section: Social Contact Social Desire and Momentary Affectmentioning
confidence: 99%
“…With young adults, Uziel et al, (2022) found that in terms of daily momentary experiences, when participants sensed that they were in the company of others by their choice, this was associated with the greatest boost to their well-being, sense of meaning, and control. In contrast, they found that when participants were alone, they experienced calmness and relative emotional stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if individuals chose to live with others due to a high social approach tendency (e.g. living with friends), there can be an opposite indirect path connecting living arrangements and daily desire for solitude via social motivation (Nikitin & Schoch, 2021; Uziel & Schmidt‐Barad, 2022). In this case, living with others would be associated with low daily desire for solitude (This was not observed in our sample—living with others was not significantly associated with extraversion, communal orientation, or preference for solitude; see Table S3).…”
Section: Discussionmentioning
confidence: 99%